Pilot Study Efektifitas Media Video Animasi Terhadap Tingkat Depresi Pasien Kanker Serviks Diagnosa Awal - Dwi Fitriyanti; Mardiyono Mardiyono; Yuriz Bakhtiar (Program Studi S1 Keperawatan Universitas Ngudi Waluyo, 2019)
Cervical cancer is the cancer that most often attacks women after breastcancer throughout the world. Around the world every two minutes or everyhour a woman dies from cervical cancer. Every patient newly diagnosed withcervical cancer needs to know information about cervical cancer that canaffect the patient's psychological changes in the form of depression. Thepurpose of this study was to determine the effectiveness of education withanimation media to reduce the depression level of cervical cancer patientswith early diagnosis. The method of this research is a pilot study(preliminary study) or testing the feasibility of animation video media on thelevel of depression. Respondent samples in the animated video media trialincluded 10 intervention samples and 10 control samples. The results of theanimation video media research are feasible to be used in subsequent studiesin cervical cancer patients with an initial diagnosis of depression. Dataanalysis using the Wilcoxon Sign Rank Test showed that there was asignificant difference in the level of depression before and after being giveneducation using the animation video media in the intervention group with avalue of p = 0.005 while in the control group with a value p = 0.102. Theconclusion of this study is that the animation video media is feasible to beused in subsequent studies and can effectively be given to cervical cancerpatients with an initial diagnosis of depression.